Validation of the E-Work Life Scale for the Portuguese population - Junça Silva, A.; Almeida, A.; Rebelo, C. (TPM - Testing, Psychometrics, Methodology in Applied Psychology, 2023)
The E-Work Life Scale (EWLS), developed by Grant et al. (2019), is an instrument used to assess the quality of life when teleworking, regarding the interference between work and personal life domains, perceptions of productivity and effectiveness, flexibility, and organizational trust. This research aims to present the validation of the EWLS to the Portuguese population, through two different studies. The goal of the first study was to explore the factor structure of the scale through exploratory factor analysis (N = 207 teleworkers). The second study (N = 272) was intended to validate the scale factor structure and analyze its convergent validity, discriminant validity, and criterion validity. The findings from both studies showed that the scale had strong reliability, and a consistent factor structure, and demonstrated convergent, discriminant, and criterion validity. Thus, we conclude that the Portuguese version of the EWLS is a valid instrument to be used among teleworkers.